2020
DOI: 10.1016/j.csbj.2020.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into the recognition of S-adenosyl-L-homocysteine and sinefungin in SARS-CoV-2 Nsp16/Nsp10 RNA cap 2′-O-Methyltransferase

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Likewise, in vitro studies showed that the extra addition of the Nsp10 protein enhances the weak Nsp14 ExoN activity (Baddock et al, 2020;Bouvet et al, 2012). In the case of Nsp16, a strong interaction of Nsp16 with Nsp10 was shown to trigger its 2 0 -O-methyltransferase (2 0 -O-MTase) activity (Bouvet et al, 2010;Imbert et al, 2008;Lin et al, 2020;Mahalapbutr et al, 2020). The direct interactions of both Nsp10-Nsp14 and Nsp10-Nsp16 were also validated by CoPIC (Figures 3 and S4), implying the importance of Nsp10 in two distinct regulatory mechanisms (Nsp14-ExoN and Nsp16-2 0 -O-MTase).…”
Section: Analysis Of the Interaction Hub Concentrated On Nsp12-nsp16mentioning
confidence: 99%
“…Likewise, in vitro studies showed that the extra addition of the Nsp10 protein enhances the weak Nsp14 ExoN activity (Baddock et al, 2020;Bouvet et al, 2012). In the case of Nsp16, a strong interaction of Nsp16 with Nsp10 was shown to trigger its 2 0 -O-methyltransferase (2 0 -O-MTase) activity (Bouvet et al, 2010;Imbert et al, 2008;Lin et al, 2020;Mahalapbutr et al, 2020). The direct interactions of both Nsp10-Nsp14 and Nsp10-Nsp16 were also validated by CoPIC (Figures 3 and S4), implying the importance of Nsp10 in two distinct regulatory mechanisms (Nsp14-ExoN and Nsp16-2 0 -O-MTase).…”
Section: Analysis Of the Interaction Hub Concentrated On Nsp12-nsp16mentioning
confidence: 99%
“…The four systems were performed with two rounds of energy minimization as reported previously by a combination of steepest descent and conjugate gradient minimizations ( Lu et al, 2019b ; Mahalapbutr et al, 2020 ; Shi et al, 2020 ; Vatansever et al, 2020 ; Wang et al, 2021a ; Lu et al, 2021b ). Afterwards, 500 ps heating, and 1,000 ps equilibration at 300 K under the NVT ensemble were performed with all heavy atoms of protein-ligand complexes fixed by a 10 kcal/(mol Å 2 ) force constant.…”
Section: Methodsmentioning
confidence: 99%
“…High conservation of the MTase site between different nidoviruses supports the idea that the catalytic site is targeted with compounds such as sinefongin [ 115 ]. Other drugs were also proposed as MTase inhibitor candidates after in silico analysis of SARS-CoV-2 NSP16 [ 117 , 118 ]. Moreover, interaction between SARS-CoV-2 NSP10 and NSP16 occurs between Val42 and Leu45 of NSP10 and two hydrophobic pockets found in NSP16.…”
Section: Structure and Function Of The Sars-cov-2 Rna Polymerase: Thementioning
confidence: 99%